Regio- and Diastereoselective Lipase-catalyzed Preparation of Acetylated 2-O-glucosylglycerols - D. COLOMBO; F. RONCHETTI; A. SCALA; I. M. TAINO; F. M. ALBINI; TOMA, LUCIO (Tetrahedron: Asymmetry, 1994)
2-O-(beta-D-Glucopyranosyl) glycerol and 2-O-(2',3',4',6'-tetra-O-acetyl-beta-D-glucopyranosyl)glycerol have been submitted to lipase-catalyzed acetylation using Pseudomonas cepacia (LPS) and Candida antarctica (LCA) lipases in organic solvent. The reactions involved the glycerol moiety and were highly diastereoselective: LPS yielded the (2S)-1-O-acetylderivative, while, more interestingly, LCA yielded the (2R)-1-O-acetyl-derivative; in this way the natural compound lilioside A could be obtained. Conversely, lipase-catalyzed hydrolysis of the fully acetylated 1,3-di-O-acetyl-2-O-(2',3',4',6'-tetra-O-acetyl-beta-D-glucopyranosyl)gl ycerol using LCA furnished the (2S)-1-O-acetyl-derivative showing the same steric preference as the reverse reaction.